Kounis Syndrome Following Beta-Lactam Antibiotic Use: Review of Literature - Ridella, Maricel; Bagdure, Satish; Nugent, Kenneth; Cevik, Cihan (Inflammation & Allergy-Drug Targets (Discontinued), 2009)
Background: Patients with anaphylaxis can have acute coronary syndromes secondary to allergic mediator effects on coronary vessels. Information about these cases is restricted to isolated case reports. Methods: To review this topic we identified all cases in the PubMed database in English with searches using betalactams adverse effects and several coronary disease MeSH terms. Results: We analyzed 17 cases with a median age of 60 (range 13 to 72). Seventy-six percent of the patients were men. The beta-lactam antibiotic was administered by oral, IV, and intramuscular routes. Thirteen patients had cutaneous reactions, seven had respiratory symptoms, two had GI symptoms, 11 had chest pain, and 12 had hypotension. All reactions except one developed within 30 minutes. Ten patients had an elevated troponin levels. ECG revealed ST segment elevation in all patients except one. Cardiac catheterization was normal in 10 patients and abnormal in five patients. Allergy testing identified four patients with positive skin tests to antibiotics, four with increased IgE levels, three with increased histamine and tryptase levels, and one with a positive leukocyte transformation test. Treatment included drugs for anaphylaxis and acute coronary syndrome. All patients survived. Conclusions: Patients with anaphylaxis can present with acute coronary syndrome secondary to either vasospasm or acute plaque rupture and thrombus formation. The typical patient is a man with cutaneous, respiratory and cardiac symptoms and with ST segment elevation in inferior leads. The pathogenesis involves histamine and other mast cell mediators. Management should include therapy for anaphylaxis and vasospasmolytics. The use of epinephrine requires caution.
Keywords: beta-lactams